Ruszt o sześciokątnej siatce prętów - GUTKOWSKI, Witold; OBRĘBSKI, Jan (Engineering Transactions, 1971)
A grill of hexagonal lattice rods The subject of this paper is an analysis of a flat grill consisting of direct elastic rods forming in a plan the lattice of equilateral hexagonals. The grill is loaded in joints with forces perpendicular to the plane of the construction and with vector moments lying in this plane. In the entire grill appear only two kinds of joints, every one of which can be obtained by removal of the other joint and turning it through about 180°. For solution of the problem was chosen a repeated element such that the equilibrium equation simultaneously describe the state in both kinds of joints. This was made possible by the consequent description of geometrical structure and by introducing the differential equations for Boole’s operators with function exponents. The work results in solution of the equilibrium equations of a joint, subject to the simplification that the rigidity of the rods for twisting is equal to 0. Also given are numerical examples.